2021
DOI: 10.3390/ijerph18041741
|View full text |Cite
|
Sign up to set email alerts
|

Chain Reversion for Detecting Associations in Interacting Variables—St. Nicolas House Analysis

Abstract: (1) Background: We present a new statistical approach labeled as “St. Nicolas House Analysis” (SNHA) for detecting and visualizing extensive interactions among variables. (2) Method: We rank absolute bivariate correlation coefficients in descending order according to magnitude and create hierarchic “association chains” defined by sequences where reversing start and end point does not alter the ordering of elements. Association chains are used to characterize dependence structures of interacting variables by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Series of coefficients of determinants that are characterized by the symmetry of ranks of R² both in forward and in backward direction are named "association chains". Thus, association chains formed are ranked according to magnitude of correlation coefficients (R 2 ), e.g., c Performance measures, the balanced classification rate and the F1score showed that SNHA was superior to methods using sophisticated correlation value thresholds and methods based on partial correlations for analyzing bands and hubs (Groth et al 2019;Hermanussen et al 2021). This technique is suitable for handling multiple correlations usually encountered in anthropometric and various socio-economic and socio-demographic variables (Groth et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Series of coefficients of determinants that are characterized by the symmetry of ranks of R² both in forward and in backward direction are named "association chains". Thus, association chains formed are ranked according to magnitude of correlation coefficients (R 2 ), e.g., c Performance measures, the balanced classification rate and the F1score showed that SNHA was superior to methods using sophisticated correlation value thresholds and methods based on partial correlations for analyzing bands and hubs (Groth et al 2019;Hermanussen et al 2021). This technique is suitable for handling multiple correlations usually encountered in anthropometric and various socio-economic and socio-demographic variables (Groth et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…St. Nicolas House Analysis (SNHA) constructs networks based on association chains of variables based on their correlations. The method has advantages as it is non-parametric and there is no need to specify a selection threshold for including variables (Groth et al 2019;Hermanussen et al 2021).…”
Section: Network Construction Methodsmentioning
confidence: 99%
“…The set contains data of variables related to the health status of 189 children and their mothers, collected at Baystate Medical Center, Springfield, Mass during 1986: age -mother's age in years, lwt -mother's weight in pounds at last menstrual period, eth -mother's ethnicity (1 = white, 2 = black, 3 = other), smo -smoking status during pregnancy (0 = no, 1 = yes), ptl -number of previous premature labours, ht -history of hypertension (0 = no, 1 = yes), ui -presence of uterine irritability (0 = no, 1 = yes), ftv -number of physician visits during the first trimester, bwt birth weight of child in grams, rndsome random uncorrelated data. For graph construction the St. Nicolas House algorithm was used(Groth et al 2019;Hermanussen et al 2021).…”
mentioning
confidence: 99%
“…After calculating all possible bivariate correlations, we performed a primary data exploration with St. Nicolas House Analysis (SNHA) (Groth et al 2019;Hermanussen et al 2021). This new statistical method is a robust non-parametric statistical tool for immediate visualization of essential associations between extensive interacting variables.…”
Section: Statisticsmentioning
confidence: 99%